Vestibular Morphological Asymmetry Associated With Motion Sickness Susceptibility - Takumi Harada (Frontiers Media S.A., 2021)
Sensory conflicts leading to motion sickness can occur not only between but also within sensory modalities. The vestibular organs are located in both left and right inner ears, and their misalignment can be a source of self-motion related sensory conflicts. In the current study, using inner ear magnetic resonance imaging, we examined whether morphological asymmetry of the bilateral vestibular organs was associated with motion sickness susceptibility. The results showed a larger position asymmetry of bilateral vestibular organs in individuals with high rather than low susceptibility. In addition, vestibular position asymmetry was associated with reciprocal interaction (negative resting state functional connectivity) between vestibular and visuocortical regions in lowly, but not highly, susceptible individuals. In conclusion, these findings suggest that vestibular morphological asymmetry can be a source of sensory conflicts in individuals with dysfunctional reciprocal visuo-vestibular interactions, a putative neural mechanism for resolving sensory conflicts.